Development of computer glossary - Dagienė, Valentina; Grigas, Gintautas (Lietuvos matematikos rinkinys, 2004)
The structure and development of hypertext computer dictionary are discussed. The glossary includes information technology terms as well as words and phrases which appears on the sceen of computer display. The glossary is published in the Internet. Descriptions of the words are comprehensive, illustrated, animation is used in some cases. The users are expected to be localizers of computer software and computer users.